If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -15 = 2x + 20 Reorder the terms: -15 + 6x = 2x + 20 Reorder the terms: -15 + 6x = 20 + 2x Solving -15 + 6x = 20 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -15 + 6x + -2x = 20 + 2x + -2x Combine like terms: 6x + -2x = 4x -15 + 4x = 20 + 2x + -2x Combine like terms: 2x + -2x = 0 -15 + 4x = 20 + 0 -15 + 4x = 20 Add '15' to each side of the equation. -15 + 15 + 4x = 20 + 15 Combine like terms: -15 + 15 = 0 0 + 4x = 20 + 15 4x = 20 + 15 Combine like terms: 20 + 15 = 35 4x = 35 Divide each side by '4'. x = 8.75 Simplifying x = 8.75
| -(8y+3)-(-7y-4)=0 | | -x/4=9 | | 0=x^2+4x-1 | | 6(2t+3)=3(11t+11) | | 6(-5x-8)=-6(6x-7) | | 0=x^2+7x+10 | | 4z-7-5z=-8 | | x^2-y^2+3x=0 | | 4t-5+8t=7(t+6) | | 30x(2x^2-1)=0 | | -8x+6+5x-1=3-14x-7+10x | | 5(y+3)=30 | | 4y+16=4 | | 5(x-1)+2=2x+11 | | -2(7-7x)=84 | | 2xy-3y=0 | | 7x+5=3x+53 | | 18+2w=7w-13 | | 2(x-1)+4=14 | | 9+3r-5=9r+13-5r | | 7(-6x+6)=42 | | 2x-4=-6x+68 | | 9-7x-6x=-30 | | 5x-3=-3x | | 9+5x+x=33 | | 22x+440=2x | | C=-5(c+6) | | 7x-7=8-8x | | 7r+19r=130 | | zr+19r=130 | | -3(x-n)=x | | y^6=6-(-2) |